Penile Angiokeratomas (PEAKERs) Revisited: A Comprehensive Review - Philip R. Cohen; Nicholas J. Celano (Adis, Springer Healthcare, 2020)
Abstract Angiokeratomas are benign vascular lesions. Genital angiokeratomas, also referred to as Fordyce angiokeratomas, usually occur on the scrotum in men and the vulva in women. Penile angiokeratoma (PEAKER) is a subtype of genital angiokeratoma in men; clitoral angiokeratoma (CLANKER) is its embryologic analog in women. The PubMed database was used to search the following words: angiokeratoma, clitoris, genital, peaker, penile, penis, rejuvenation, scrotal, scrotum and vulva. The relevant papers and references cited in those papers that were generated by the search were reviewed. The purpose of this article is to summarize the features of PEAKERs. PEAKERs have been described in 54 men. They usually appeared in younger men and had been present for a mean duration of 4 years prior to the individual seeking medical attention. Only 39% of the men had angiokeratoma-associated symptoms: usually bleeding and increasing size and less often abrupt onset, pain and pruritus. The glans penis (55.5%) and the penile shaft (35%) were the most common sites of PEAKERs; the angiokeratomas were also located on the foreskin (5.5%) or both the glans penis and penile shaft (4%). Thirty seven percent of patients with glans penis PEAKERs only had angiokeratomas on the corona. Scrotal angiokeratomas were also present in 20% of patients with PEAKERs. A solitary PEAKER was observed in 32% of the men. Most of the PEAKERs were 1-5 mm in size. The PEAKERs presented as purple, red and/or blue papules; 70% of the men's PEAKERs were more than one color. Clinical features often established the diagnosis; in addition, some of the men's angiokeratomas were biopsied or evaluated with dermoscopy. Laser therapy, in 56% of the men, was the most common treatment modality. Less common interventions included electrocautery, radiofrequency and excision. PEAKER recurrence or persistence was observed after excision (two men) or cryotherapy (one man), respectively. Several of the men (27%) decided to observe their PEAKERs without treatment.